Characteristics of board and shariah board on risk-taking and performance: evidence from Takaful operators in Malaysia - Ainulashikin Marzuki; Nurul Nazlia Jamil; Muhamad Azhari Wahid; Wan Amalina Wan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines how board of directors (BOD) and Shariah board (SB) characteristics influence risk-taking and performance in Malaysian Takaful operators (TOs). These operators face unique challenges when balancing financial growth with strict adherence to Shariah principles. The study analyse data from 15 TOs from 2012 to 2021, resulting in a total of 124 firm-years of observations using panel data regression techniques. The key findings are a higher proportion of women on BOD leads to less risk-taking, while larger SB with more PhD members encourage it. However, the impact on performance is mixed. More women on BOD might reduce returns on assets, while frequent BOD meetings and a highly qualified SB might lower return on equity. This research offers valuable insights, where investors should consider the risk-return trade-off when evaluating TOs based on BOD and SB composition while managers need to balance risk management with Shariah compliance by building diverse BOD and optimising SB structure. Industry regulators should promote sound governance practices and collaboration between BOD and SB. Overall, the study contributes to the corporate and Shariah governance literature, shedding light on the complex interplay between BOD composition, SB expertise, risk-taking and performance in a complex industry.